PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN SCRAMBLE PADA MATERI TATA NAMA SENYAWA BINER - Ade Kurnia; Rini Muharini; Lukman Hadi (Universitas Tanjungpura, 2020)
AbstractThe ability of teachers to use appropriate learning models in their classes is essential to improve student’s achievements. The purpose of this research was to determine the difference in study result and the influence of the learning model scramble to the study procces of students of Class X SMK SMTI Pontianak. This research design was quasi-experimental research with nonequivalent control group design. Engineering sample selection was done by cluster random sampling technique. The tools of data collection used on this research were test items, observation and interview sheet. The result showed that there was difference significantly in study result between the two classes, learners who were taught using conventional learning model and learners who were taught using scramble learning model. Based on the calculation of effect size, scramble learning model in nomenclature binary compounds material gave a value of 1, 2023 which had a high influence on the study of students of class X SMK SMTI Pontianak.Keywords: Difference in Study Result, Learning Model Scramble, Nomenclature Binary Compounds